The implementation of the new capital accord (BASEL II) : a comparative study of South Africa, Switzerland, Brazil and the United States - Makwiramiti, Anthony Munyaradzi (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
The international banking environment has become potentially riskier because of the recent developments in financial services and products which have changed the way banks do their day to day business. Imposing minimum capital adequacy regulations is one way of fostering stability in the global banking system. A number of countries have started to implement the new capital adequacy rules (Basel II) following the worldwide consensus among central bankers that bank"Ÿs capital levels should be regulated to enhance global financial stability. In this study, through the comparative analysis of the general implementation issues it was established that emerging countries apply all Basel II rules uniformly across all the banking institutions that operate in their territories. Developed countries apply these rules only to large and internationally active banks and because of the diversity of their banking industries, they also apply domestically modified rules to the domestically based banks. For the successful implementation of Basel II, properly planning, devoting bank resources and making necessary legislative amendments are prerequisites for incorporating Basel II into the regulatory framework for any country. The study concludes that the current global financial turmoil continues to pose a threat to the effectiveness of the Basel II rules which are aimed at achieving global financial stability.
Keywords: Basel II (2004); Banks and banking, International; Banks and banking, International -- State supervision; Capital market -- Government policy; Bank capital; Banking law; Financial institutions